Immunoglobulin E-Mediated Autoimmunity - Maurer, Marcus; Altrichter, Sabine; Schmetzer, Oliver; Scheffel, Jörg; Church, Martin K.; Metz, Martin (Frontiers in Immunology, 2018)
The study of autoimmunity mediated by IgE autoantibodies, which may be termed autoallergy, is in its infancy. It is now recognised that systemic lupus erythematosus, bullous pemphigoid and chronic urticaria, both spontaneous and inducible, are most likely to be mediated, at least in part, by IgE autoantibodies. The situation in other conditions, such as autoimmune uveitis, rheumatoid arthritis, hyperthyroid Graves' disease, autoimmune pancreatitis, and even asthma, is far less clear but evidence for autoallergy is accumulating. To be certain of an autoallergic mechanism, it is necessary to identify both IgE-autoantibodies and their targets as has been done with the transmembrane protein BP180 and the intracellular protein BP230 in bullous pemphigoid and IL-24 in chronic spontaneous urticaria. Also, IgE-targeted therapies, such as anti-IgE, must have been shown to be of benefit to patients as has been done with both of these conditions. This comprehensive review of the literature on IgE-mediated autoallergy focuses on three related questions. What do we know about the prevalence of IgE autoantibodies and their targets in different diseases? What do we know about the relevance of IgE autoantibodies in different diseases? What do we know about the cellular and molecular effects of IgE autoantibodies? In addition to providing answers to these questions, based on a broad review of the literature, we outline the current gaps of knowledge in our understanding of IgE autoantibodies and describe approaches to address them.